Konsep Pengembangan Kampung Batik Durenan Indah Suatu Pendekatan Antropologi Terapan - Eko Punto Hendro (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
Kampung Batik Durenan Indah Batik is a gathering place for batik artisans, which number around 20 people who are members of four companies. Recently batik artisans participated in the provincial level industry of craft competition because they had previously won the city level race. The approach used in research is applied anthropology, with observation and in-depth interviews. On a more modern entrepreneurial scale, they are still at the beginner level, because they have not used a professional business management system. However, the spirit of the craftsmen is quite high, it requires assistance and direction from the government and other related partie